Can we win the fight? - Abd Razak, Dzulkifli (2006)
The 'Belia Benci Dadah' programme has only a slim chance to succeed like the 'Tak Nak' antismoking campaign. AFTER the controversy over " Predator", the "date rape" drug, now we are faced with the "dance and sex" drug, according to the warning issued by the United Nations drug control agency last week. While the "Predator" refers to drugs such as Rohypnol, GHB (gamma hydroxy butyrate) and ketamine hydrochloride, the dance and sex variety belongs to the group of amphetaminetype stimulants (ATS). While the "Predator" renders the users incapable of asserting themselves and saying "no" to suggestions that can lead to sexual abuse such as rape, the ATS intends to keep the users wide awake for days. This can lead to violent behaviour, anxiety, mood swings, paranoia as well as fever, convulsions and selfharm. It can cause death from an increase in blood pressure, resulting in the bursting of blood vessels in the brain and heart failure.